2013
DOI: 10.1111/apha.12073
|View full text |Cite
|
Sign up to set email alerts
|

Differential developmental programming by early protein restriction of rat skeletal muscle according to its fibre‐type composition

Abstract: We conclude that maternal protein restriction alters in the long term the structural and enzymatic properties of offspring skeletal muscle in a fibre-type-dependent manner. These alterations might have a causative role in the development of obesity and related metabolic disorders later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
(103 reference statements)
1
10
0
Order By: Relevance
“…The effect of maternal protein restriction during pregnancy and lactation on fiber-type composition of skeletal muscle in rats was studied by da Silva et al Rats fed a normal protein diet (17% protein) exhibited enhanced density of type II fibers along with a decreased rate of fatty acid oxidation and glycolysis in the soleus but not the extensor digitorum longus (EDL) in the lower leg compared with rats that were fed a low protein diet (7%). Authors suggested that protein restriction alters the structure and enzymatic properties of skeletal muscle with a potential role in the development of obesity and its comorbidities as fiber-type composition of skeletal muscle is associated with obesity and insulin resistance [ 78 ].…”
Section: Maternal Protein Intake and Fetal Programmingmentioning
confidence: 99%
“…The effect of maternal protein restriction during pregnancy and lactation on fiber-type composition of skeletal muscle in rats was studied by da Silva et al Rats fed a normal protein diet (17% protein) exhibited enhanced density of type II fibers along with a decreased rate of fatty acid oxidation and glycolysis in the soleus but not the extensor digitorum longus (EDL) in the lower leg compared with rats that were fed a low protein diet (7%). Authors suggested that protein restriction alters the structure and enzymatic properties of skeletal muscle with a potential role in the development of obesity and its comorbidities as fiber-type composition of skeletal muscle is associated with obesity and insulin resistance [ 78 ].…”
Section: Maternal Protein Intake and Fetal Programmingmentioning
confidence: 99%
“…It is also estimated that foetal undernutrition causes mitochondrial dysfunction (Reusens et al 2011b), as well as telomere shortening (Tarry-Adkins et al 2009) in the pancreas resulting in lower energy synthesis and an inadequate antioxidant balance which might consequently lead to metabolic syndrome. Recent studies have linked changes in the skeletal as well as cardiac muscle composition with later cardiovascular pathogenesis (Tarry-Adkins et al 2013;da Silva Aragao et al 2014). The above changes demonstrate that early nutrition might have a dramatic impact on all organ systems at a cellular as well as the subcellular level.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors have shown that muscle fibers are capable of adapting their metabolism, optimizing protein turnover to preserve the primary functions in malnutrition conditions [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%